The Improvement of Low Salt Diet Behavior based on Theory of Planned Behavior on Elderly with Hypertension - Lembunai Tat Alberta; Jujuk Proboningsih; Masamah Almahmudah (Universitas Airlangga, 2014)
Introduction: Hypertension in elderly is triggered by the thickening and stiffness of arterial wall due to ageing processes. One attempt to prevent the complications of hypertension is by change their lifestyle, such as perform a low-salt diet. The implementation of a low-salt diet on elderly should be adjusted with their behavior and habits. TPB is one of theoretical attempt to identify the relationship between elderly’s attitude and their behavior, and to emphasize the importancy of intention as determinant of behavior, focused on cognitif and rational decission making process. This study was aimed to analyze the improvement of low salt diet behavior based on TPB on elderly with hypertension.Method: This research was used descriptive design with observational analytic method. Population were elderly with hypertension recorded at Puskesmas Pucang, Kota Surabaya. Samples were 32 respondents, taken randomly. Data were collected by using questionnaires and direct interview. Data were then analyzed by using Partial Least Square (PLS).Result: The results had showed that intention to implement a low-salt diet was built by attitudes toward behavior, subjective norms, and perceived behavioral control (PBC) on elderly with hypertension. A low-salt diet behavior was built by intention to implement a low-salt diet on elderly with hypertension.Discussion: These results can be used as a model to improve low salt diet behavior on elderly with hypertension.